Diagnosis and Management of Anemia in The Elderly - Pratiwi Anggraini; Theophany Margareta Kurniawan; Ima Arum Lestarini (Jurnal Biologi Tropis, 2023)
Anemia is one of the hematological disorders that can contribute to increased morbidity and mortality in the elderly because it can be a risk factor for various other diseases so that accurate diagnosis and appropriate management are needed. This literature review aims to provide related information, so that proper diagnosis and management for anemia in the elderly can be carried out to reduce morbidity and mortality rates. In this literature review we conducted a search on the PubMed database using the search keyword "Anemia in The Elderly". Diagnosis of anemia in the elderly begins with recognizing signs and symptoms which is then followed by laboratory examination to determine the etiology of the disease. Several other examinations such as spinal cord aspiration, endoscopy, or ultrasound can be done depending on the need. Management of anemia in the elderly is carried out by administering iron supplementation both orally and intravenously. Other treatments such as erythropoiesis-stimulating agents (ESA) and blood transfusions can be done according to indications. Establishing the diagnosis of anemia in the elderly can be done by anamnesis, physical examination, to laboratory examination.